2008
DOI: 10.1002/jcc.21032
|View full text |Cite
|
Sign up to set email alerts
|

Global dynamics and transition state theories: Comparative study of reaction rate constants for gas‐phase chemical reactions

Abstract: In this review article, we present a systematic comparison of the theoretical rate constants for a range of bimolecular reactions that are calculated by using three different classes of theoretical methods: quantum dynamics (QD), quasi-classical trajectory (QCT), and transition state theory (TST) approaches. The study shows that the difference of rate constants between TST results and those of the global dynamics methods (QD and QCT) are seen to be related to a number of factors including the number of degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
47
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(58 citation statements)
references
References 169 publications
11
47
0
Order By: Relevance
“…Their study showed a very good agreement between the QCT and the previous quantum calculations [15]. Moreover, as revealed in previous studies [37,38], there exists qualitative agreement between QCT and quantum calculations for many reactive systems. Therefore, QCT method can provide reliable dynamical quantities in many cases and thus can be used here as an efficient tool for dynamics exploration.…”
Section: Resultssupporting
confidence: 65%
“…Their study showed a very good agreement between the QCT and the previous quantum calculations [15]. Moreover, as revealed in previous studies [37,38], there exists qualitative agreement between QCT and quantum calculations for many reactive systems. Therefore, QCT method can provide reliable dynamical quantities in many cases and thus can be used here as an efficient tool for dynamics exploration.…”
Section: Resultssupporting
confidence: 65%
“…Similarly, the rate equation can be deduced into a same functional form as the experiment observation (6) when Considering the above analysis, the TS2 step of the channel 1 has very low barrier and hence high rate (~ 10 11 s -1 ), while the protonation process is generally low barrier or no-barrier just judged from the usual observations in experiments and calculations [29,30]. Such low barrier protonation process of the bimolecular reaction belongs to diffusion-controlling reaction in various solvents (k d ≈ 10 9 -10 11 M -1 s -1 ) [30].…”
Section: Reaction III (R 1 = Me R 2 = O - R 3 = Me)mentioning
confidence: 89%
“…Such low barrier protonation process of the bimolecular reaction belongs to diffusion-controlling reaction in various solvents (k d ≈ 10 9 -10 11 M -1 s -1 ) [30]. Therefore, in low-viscosity solvents, the two channels may coexist, while in high-viscosity medium, the diffusionrate reduces greatly which results in the bimolecular protonation reaction can hardly compete with the monomolecular reaction of TS2 step in the channel 1.…”
Section: Reaction III (R 1 = Me R 2 = O - R 3 = Me)mentioning
confidence: 99%
“…[14,[16][17][18][19][20][21][22][23][24][26][27][28][29][30]. The classical Hamilton's equations are numerically integrated in three dimensions.…”
Section: Theorymentioning
confidence: 99%